A.D. Deikina’s scientific school: conceptual role of axiological approach in Russian language teaching - Olga V. Alekseeva (Russian Language Studies, 2019)
The article describes the issues of axiological linguodidactics exemplified in methodical studies of A.D. Deikina’s scientific school: linguistic substantiation of axiological aspect in Russian language teaching, culturological component of pupils’ value system, new technologies for axiological skills development at Russian language lesson, philology students’ value system development as a professional competence. Conceptual features have been defined in scientific school research: focus on personality development, social experience acquisition, training the aptitude to various cooperation with the surrounding community. The scientific school works reflect conceptual development of linguistic and methodical training for Russian language teachers, focused on increasing pupils’ learning and cognitive motivation and improving their personal, metasubject and subject achievements. The scientific novelty of the research is defined by the key idea of anthropocentricity, integrity of essential components of axiological methodology, multifacetedness of approaches to text-oriented language studies. The scientific research in the article shows the development of Russian language teaching methodology in the first decades of the XXI century. The value of the article for contemporary school education lies in the fact that axiological linguistic methodology assists in developing cultural identity of future Russian citizens.